1997
DOI: 10.1093/oxfordjournals.aob.a010307
|View full text |Cite
|
Sign up to set email alerts
|

Laser-driven Photoacoustic Spectroscopy: What We Can Do with it in Flooding Research

Abstract: Photoacoustic spectroscopy is a highly sensitive technique for measuring low molecular weight gases such as the plant hormone ethylene. Due to its high sensitivity (10 pl 1 -ethylene), photoacoustic spectroscopy can be combined with flow-through systems that avoid the need for enclosing excised plant parts in small volumes for head-space analysis. In this way, artifacts introduced by various accumulation techniques can be avoided and ethylene production monitored at short intervals in air or other gas mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…A similar high ethylene evolution in the dark was also observed for partially submerged deepwater rice (Stu$ nzi & Kende, 1989) and completely submerged R. palustris plants (Banga et al, 1996). Oxygen levels found inside petiole tissue during dark periods in our study are comparable with the low levels applied in Voesenek et al (1997a). This indicates that submergence-induced changes in endogenous O # levels are likely to be responsible for the reversal of daily elongation rate.…”
Section: supporting
confidence: 88%
See 1 more Smart Citation
“…A similar high ethylene evolution in the dark was also observed for partially submerged deepwater rice (Stu$ nzi & Kende, 1989) and completely submerged R. palustris plants (Banga et al, 1996). Oxygen levels found inside petiole tissue during dark periods in our study are comparable with the low levels applied in Voesenek et al (1997a). This indicates that submergence-induced changes in endogenous O # levels are likely to be responsible for the reversal of daily elongation rate.…”
Section: supporting
confidence: 88%
“…100-fold (Voesenek et al, 1993a ;Banga et al, 1996). Oxygen can influence, in at least two ways, the process of stimulated petiole elongation ; sub-ambient O # concentrations can sensitize petiole tissue to ethylene (Blom et al, 1994 ;Voesenek et al, 1997a), and can reduce the rate of ethylene production because of the requirement of molecular oxygen for the conversion of 1-aminocyclopropane-1-carboxylic acid (ACC) to ethylene catalysed by ACC oxidase (Yang & Hoffman, 1984 ;Kende, 1993 ;Banga et al, 1996). Furthermore, leaf elongation rate of R. palustris through the day was found to change dramatically when exogenous O # concentration was altered ; in norm-oxic conditions elongation rate increased during the dark period and decreased in the light, whereas in a 3 kPa O # atmosphere maximum elongation rates were found well into the light period (Voesenek et al, 1997b).…”
Section: mentioning
confidence: 99%
“…Prompt biosynthesis of ethylene after hypoxia has been observed in Rumex in previous studies (Voesenek et al . , ). In contrast to ACO1 , ACO2 was mainly induced during reoxygenation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the production of ethylene is increased in de-submerged or post-hypoxic Rumex (Voesenek et al 1997(Voesenek et al , 2003. Recently, it was reported that ethylene was synthesized during reoxygenation in partially submerged cucumber roots (Garcia et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly they have insufficient water, however they are often exposed to excess water. Flooding or waterlogging can occur during partial or total submersion of plants in running or stagnant water and can subject the plants to considerable periods of anaerobiosis (Andrews 1977, Voesenek et al 1997. M a n y higher plants respond to the anareobiosis by altering the respiratory metabolism and the related gene expression (Sachs andHo 1986, Millar et al 1994).…”
Section: Introductionmentioning
confidence: 99%